ANALISA PRAKTIK AKAD ISTISHNA TERHADAP JUAL BELI FIBER OPTIK PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM: Studi di PT Smart Innovation Technology - Eri Herdiansyah; Irvan Iswandi (Melati Institute, 2022)
PT. Smart Innovation Technology is a company formed by the idea and desire to increase advance technology in telecommunication field and Industry in Indonesia. In its journey, PT. Smart Innovation Technology could show its capability and quality by owning some patents, certificates, and international awards. It is also trusted as the consultant and work partner by many big companies in Indonesia. The purpose of this research was to find out the practice of Istishna Agreement in Optical Fiber Commerce at PT. Smart Innovation Technology if it is already in line with Positive Law and Islamic Law or not. In this undergraduate thesis, the researcher employed qualitative method which aimed to understand the social situation, event, role, interaction and group, and it gives current information until it is beneficial for the development of science and further to be applied in various field. From the research which had been conducted by the author, obtained the result that in the practice of Istishna agreement in Optical Fiber Commerce at PT. Smart Innovation Technology has been in line with the provision of Positive Law and Islamic Law. The transaction practiced between PT. Smart Innovation Technology as the seller and the client as the buyer had the deal first either price, specification, processing time, and goods handover.